The coesite–stishovite transition of hydrous, Al-bearing SiO2: an in situ synchrotron X-ray study - M. Koch-Müller; C. Lathe; B. Wunder; O. Appelt; S. Bhat; A. Ebert; R. Farla; V. Roddatis; A. Schreiber; R. Wirth (European Journal of Mineralogy, 2024)
We examined the influence of Al2O3 and H2O on the position of the coesite–stishovite transition by means of in situ X-ray diffraction measurements with the large-volume press at the PETRA III synchrotron in Hamburg. The position of the transition was determined by several reversal experiments and was found to be shifted almost in parallel by about 1.5 GPa to lower pressures compared to results for the pure SiO2 system reported by Ono et al. (2017). Two further reversal experiments with either additional Al2O3 or additional H2O added to SiO2 showed smaller changes compared to the results of Ono et al. (2017), indicating the effect of the coupled Al and H incorporation in coesite and stishovite on their transition. Further investigations of the solid quenched products and of products from additional multi-anvil experiments performed at the GFZ Helmholtz-Zentrum für Geoforschung in Potsdam were done by powder X-ray diffraction (XRD), transmission electron microscopy (TEM), electron probe micro-analysis (EPMA), and Fourier transform infrared (FTIR) and Raman spectroscopy. Generally, the recovered samples of the in situ experiments contained less stishovite than expected from the last in situ XRD pattern before quenching. Thus, these investigations clearly show that hydrous, Al-rich stishovite that formed at high pressure (P) and temperature (T) could, at least partly, not be quenched to room conditions and transformed to coesite with unusually high (Al, H) contents. As result of this, conventional quench experiments would lead to erroneous results of the transition in the (Al, H)-bearing SiO2 system. We observed two kinds of coesite in the experiments: one relatively Al-poor coesite transformed under equilibrium conditions at P and T from stishovite over a certain time frame and an Al-richer one, sometimes pseudomorphically replacing former stishovite during the decompression process to room conditions. Within both types of coesite, nanometre-sized kyanite inclusions and relicts or remnants of stishovite were observed by TEM. These observations resemble those of Yang et al. (2007) on ophiolites with identical textures and phases and were interpreted as result of a stishovite transition back to coesite during retrograde metamorphism. Our results clearly indicate that the coesite–stishovite transition is sharp but can considerably vary in depth by the addition of Al and H to the SiO2 system. This has consequences for the assignment and interpretation of the depth variation of the seismic X discontinuity.